Hyperproduction of 3-hydroxypropionate by Halomonas bluephagenesis - Xiao-Ran Jiang (Nature Portfolio, 2021)
3-Hydroxypropionic acid (3HP) is an important platform chemical. Here, the authors engineer Halomonas bluephagenesis by deleting newly identified degradation pathway and balancing redox state to achieve high level production of 3HP and its copolymer under open and unsterile conditions.